(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The impact of environmental degradation and health inequity has raised the need for sustainable healthcare sytems. Though policies and technology address the healthcare challenges, ethical and value based foundatons are neglected. Linking the healthcare with spiritaulity will help in understanding the interconnectedness, compassion, orientation for life and moral frame work for practicing sustainable healthcare. This article examines the conceptual and practical relationship between spirituality and sustainability in healthcare, taking examples from Indian context. The study draws on philosophical traditions, environmental ethics, and case studies, including the Chipko Movement, practices of the Bishnoi community, sacred groves, Gandhian philosophy, and traditional medicine systems like Yoga and Ayurveda. The study highlights on the points that achieving sustainable healthcare necessitates both systemic change and moral growth among healthcare professionals and communities. By integrating spiritual values into healthcare sustainability initiatives, we can provide a holistic pathway for achieving ecological reponsibility, social equity and patient well-being.